2021
DOI: 10.1007/s11356-021-15225-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The non-linear relationship between carbon dioxide emissions, financial development and energy consumption in developing European and Central Asian economies

Abstract: Graphical abstract A sizeable amount of scholarly work has been done on different aspects of financial, economic, and environmental factors. In the present study, the nonlinearity is determined between financial development and carbon dioxide emissions in the long-run and short-run periods. According to the finding, the continued financial development initially increases the carbon dioxide emissions in the short and long run. Simultaneously, the square term of financial development reduces carbon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Environmental efficiency means simultaneously maximizing good outputs whiles minimizing the use of inputs such as energy, labor, etc., and bad outputs such as CO 2 (Long et al 2017 ). A number of studies have been conducted on environmental efficiency in Asia and other parts of the world including the effect of renewable energy consumption (Jiang et al 2022 ), relationship between carbon dioxide emissions, financial development and energy consumption (Chunyu et al 2021 ), and the correlation between ICT, renewable energy, financial development, and CO2 emissions (Batool et al 2022 ). Previous studies have used the Malmquist Luenberger Productivity Index and Data Envelopment Analysis (DEA) to estimate environmental efficiency in China (Piao et al 2019 ), as well as the SBM Metafrontier to estimate the effect of fertilizer usage intensity on environmental efficiency (Long et al 2018 ).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Environmental efficiency means simultaneously maximizing good outputs whiles minimizing the use of inputs such as energy, labor, etc., and bad outputs such as CO 2 (Long et al 2017 ). A number of studies have been conducted on environmental efficiency in Asia and other parts of the world including the effect of renewable energy consumption (Jiang et al 2022 ), relationship between carbon dioxide emissions, financial development and energy consumption (Chunyu et al 2021 ), and the correlation between ICT, renewable energy, financial development, and CO2 emissions (Batool et al 2022 ). Previous studies have used the Malmquist Luenberger Productivity Index and Data Envelopment Analysis (DEA) to estimate environmental efficiency in China (Piao et al 2019 ), as well as the SBM Metafrontier to estimate the effect of fertilizer usage intensity on environmental efficiency (Long et al 2018 ).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Former studies argued that conventional energy consumption increases carbon emissions through the excessive use of fossil fuels in industrialization, urbanization, transportation, and other economic activities. Thus, a positive relationship exists between non-renewable energy consumption and environmental pollution (Khan et al, 2020;Chunyu et al, 2021). Saboori and Sulaiman (2013) empirically analyzed the influence of energy consumption on environmental pollution in Malaysia and found that high consumption of non-renewable energy sources leads to CO 2 emissions.…”
Section: Non-renewable Energy Consumption and Environmentmentioning
confidence: 99%
“…It is also called clean energy and includes different forms such as solar, wind, hydro, tidal and geothermal. However, many past studies found that using conventional energy degrades the environment (Chunyu et al, 2021;Fatima et al, 2021). In order to achieve rapid economic growth and compete in the foreign market with more productivity and low cost, developing countries frequently use non-renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, FDI and fossil fuel energy consumption are also significant contributors to the economic growth of developing Asian countries (Huang et al, 2020). Moreover, a non-renewable form of energy taken as fossil fuels significantly increases carbon emissions in European and Central Asian developing economies (Chunyu et al, 2021). In South Asian economies, non-renewable energy contributes to the ecological footprint (Xue et al, 2021).…”
Section: Literature Review Fdi Energy and Environmentmentioning
confidence: 99%